A Study on Tax Non-Compliance among Government Servants - Rosmaria, Jaffar @ Harun; Izah, Mohd Tahir; Ku Naraini, Che Ku Yusof; Mohd Jaffri, Abu Bakar (2014)
Tax non-compliance among tax payers may have an impact on the collection of tax revenue. In other words, the revenue collected may not represent the number of tax payers. The objectives of this study are to investigate the relationship between demographic factors and tax non-compliance, to analyze the attitude of tax noncompliance among individual taxpayerand to explore the reasons of non-compliance. A structured questionnaire consisted of 29 closed-ended question were posted to 200 respondents who worked in the Institutions of Higher Learning, Government Link Company and State-owned Company. The results found that single person, middle income earners, highly educated and respondents from State Owned Company are more tax-compliance compared to respondents who are married, lower and higher income earners, lower education and working other than state-owned company. The main reason given for non-compliance is the amount of taxes to be paid is considered to be too high.